Increased serum IgE concentrations during infection and graft versus host disease after bone marrow transplantation. Issue 4 (April 1984) - Walker, S A; Rogers, T R; Perry, D; Hobbs, J R; Riches, P G
Abstract : Serum IgE concentrations estimated in 25 bone marrow transplant recipients during episodes of infection or graft versus host disease, or both, were raised not only in some patients with acute graft versus host disease but also in many patients with infection. Raised values were not seen in chronic graft versus host disease. The routine estimation of serum IgE in bone marrow transplant recipients had minimal value because of the lack of specificity of the IgE response.